Three Intervention Programs in Secondary Education on Attitudes Toward Persons With a Disability - Álvarez-Delgado, Julián; León-del-Barco, Benito; Polo-del-Río, María-Isabel; Mendo-Lázaro, Santiago; Lopez-Ramos, Victor M. (Frontiers in Psychology, 2022)
Persons with a disability make up a social group which is in an especially vulnerable situation. They have to face obstacles and difficulties in their participation as part of the community with equal opportunities, in which attitudes of others is a determining factor. This study makes a comparative analysis of three intervention programmes (1 “simulation and modelling”, 2 “information and awareness-raising” and 3 “adapted sport”) on attitudes towards persons with a disability of adolescents in secondary schools. Each programme is based on a concrete technique, but they all have the common thread of the direct, structured contact technique with persons with a disability. The effectiveness of the three programmes in changing attitudes is analysed and their impact on the different factors of the attitude construct (1 “acceptance-rejection”, 2 “competence/limitation” and 3 “equality of opportunities”) is also studied. The results show the effectiveness of the three programmes. The students show more positive attitudes towards persons with a disability in all the groups, especially programme 1. Analysing the general influence of the three programmes on the factors of the attitude construct, it can be seen that in factors 2 and 3, the attitudes have significantly improved in all three programmes. Finally, the results show that each programme has been more effective on a concrete attitude factor.